C + L band extended reach amplified next generation access networks - Girão, J. P.
The feasibility of optical amplification solutions for extended reach next generation access networks in C + L bands is studied. Amplification schemes based on Raman fiber amplifier and their combination with remotely pumped erbium-doped fiber amplifiers are assessed and optimized. The results concerning a ring with 80 km for rural scenario demonstrate gain equalization over a bandwidth of 50 urn. The survey was complemented with experimental results. (C) 2011 Wiley Periodicals, Inc. Microwave Opt Technol Lett 53:2414-2418, 2011; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.26251